Cross-Sectional Assessment of Achievement of Therapeutic Goals in a Canadian Multidisciplinary Clinic for Patients With Advanced Chronic Kidney Disease. Issue 1 (11th May 2018) - Rinfret, Félix; Lambert, France; Youmbissi, Joseph Tchetagni; Arcand, Jean-François; Turcot, Richard; Bessette, Maral Alimardani; Bourque, Solange; Moreau, Vincent; Tousignant, Karine; Deschênes, Diane; Cloutier, Lyne
Background: The implementation of advanced chronic kidney disease (CKD) multidisciplinary clinics has now demonstrated their effectiveness in delaying and even avoiding dialysis for patients with CKD. However, very little has been documented on the management and achievement of targets for a number of parameters in this context. Objective: Our goal was to assess our multidisciplinary clinic therapy performance in relation to the targets for hypertension, anemia, and calcium phosphate assessment. Methods: Design and setting: A cross-sectional descriptive study was conducted with a cohort including all patients followed up in our multidisciplinary clinic in July 2014. Measurements: Comorbidity, laboratory, and clinical data were collected and compared with the recommendations of scientific organizations. Results: The cohort included 128 patients, 37.5% of whom were women. Mean follow-up time was 26.6 ± 25.1 months and mean estimated glomerular filtration rate (eGFR) was 14.0 ± 4.7 mL/min/1.73 m 2 . A total of 24.2% of patients with diabetes achieved blood pressure targets of <130/80 mm Hg, while 56.5% of patients without diabetes achieved targets of <140/90 mm Hg. Hemoglobin of patients treated with erythropoiesis-stimulating agents was 100 to 110 g/L in 36.2% of the patients, below 100 for 39.7% of them, and above 110 for 24.1%, whereas 67.2% were within the acceptable limits of 95 to 115 g/L. In addition, 63.4% of patients had a serum phosphate of <1.5 mmol/L, and 90.9% of patients had total serum calcium <2.5 mmol/L. Limitations: Our study is a single center study with the majority of our patients being Caucasian. This limits the generalizability of our findings. Conclusion: The control rates of various parameters were satisfactory given the difficult clinical context, but could be optimized. We publish these data in the hope that they are helpful to others engaged in quality improvement in their own programs or more generally.